The Jaga Jakarta Task Force as a Collaborative Governance Model Under the Governor Decree of the Special Capital Region of Jakarta Number 997 of 2025 - Ericko Pandu Sumbogo; Arthur Josias Simon Runturambi; Husnul Fitri (Eduvest - Journal of Universal Studies, 2026)
Mass fights disrupt urban security, and the government cannot handle them alone. This study aims to analyze the Jakarta Guard Task Force as a collaborative governance model based on the Decree of the Governor of the Special Region of Jakarta Number 997 of 2025 in an effort to prevent mass fights in the Special Region of Jakarta. The research uses a qualitative approach with the Systematic Literature Review (SLR) method through the study of academic literature, policy documents, and relevant regulations. The analysis was conducted using Ansell and Gash's Collaborative Governance theory which includes starting conditions, facilitative leadership, institutional design, collaborative process, and intermediate outcomes. The results of the study show that the Jakarta Guard Task Force represents a collaborative governance model that integrates local governments, security forces, intelligence elements, regional apparatus organizations, and the community in one urban security management system. Collaboration is realized through cross-sector coordination, information exchange, early detection of social conflicts, joint patrols, and community involvement in efforts to prevent mass fights. In conclusion, the implementation of collaborative governance in the Jakarta Guard Task Force has the potential to increase the effectiveness of preventing social conflicts through strengthening inter-agency coordination, increasing community participation, and developing a more preventive and participatory security system. The implications suggest that collaborative governance is relevant for complex urban security and can serve as a reference for other regions.